2014
DOI: 10.1038/oncsis.2014.12
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-18a is elevated in prostate cancer and promotes tumorigenesis through suppressing STK4 in vitro and in vivo

Abstract: MicroRNAs (miRNAs) comprise a class of short, non-coding RNAs that regulate protein synthesis through posttranscriptional modifications. In this study, we found significant upregulation of miR-18a in prostate cancer specimens and prostate cancer cell lines compared with the normal controls. MiRNAs can be separated into two groups based on whether they regulate tumor suppressors or oncogenes. In our previous study, we found that miR-18a, which belongs to the miR17-92 cluster, is upregulated in prostate cancer; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
95
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 43 publications
3
95
0
Order By: Relevance
“…miR-18a belongs to the miR17-92 gene cluster, of which HIF-1α is a target gene (16). It has been reported that miR-18a serves a crucial function in the occurrence and development of myocardial ischemia (17), colonic neoplasm (18), liver tumors (19), prostate cancer (20) and malignant gliomas (21). Furthermore, a previous study suggests that miR-18a may be a specific biomarker for the early diagnosis and treatment of tumors (22).…”
Section: Discussionmentioning
confidence: 99%
“…miR-18a belongs to the miR17-92 gene cluster, of which HIF-1α is a target gene (16). It has been reported that miR-18a serves a crucial function in the occurrence and development of myocardial ischemia (17), colonic neoplasm (18), liver tumors (19), prostate cancer (20) and malignant gliomas (21). Furthermore, a previous study suggests that miR-18a may be a specific biomarker for the early diagnosis and treatment of tumors (22).…”
Section: Discussionmentioning
confidence: 99%
“…The present study evaluated the levels of miR-18a, a highly expressed miRNA in the tissues of PC (16), in the peripheral blood of patients with PC or BPH, and in healthy individuals, to test the feasibility of using peripheral blood miR-18a as a potential novel non-invasive biomarker for PC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miRNA (miR)-18a, which is located in the potentially oncogenic miR-17-92 cluster (12,13), is highly expressed in various types of cancer (13)(14)(15). Furthermore, miR-18a has recently been demonstrated to act as an oncogenic miRNA in PC by promoting tumorigenesis in in vitro and in vivo models of PC (16).…”
Section: Introductionmentioning
confidence: 99%
“…miRNA expression can be associated with a variety of cancer, either functioning as oncogene or tumor suppressor. miR-15a, 16-1,17-5p,143,145, and let-7 were identified as a tumor suppressor while miR-18a,19a-b, 20a,21,92,155, and 372 were known as oncomiRs [3,4]. Indeed, miRNA has showed potential value in cancer diagnosis and therapy.…”
Section: Introductionmentioning
confidence: 99%